2023
DOI: 10.3390/su151813904
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Evapotranspiration and Its Driving Factors in the Urumqi River Basin

Kamila Ablikim,
Han Yang,
Azimatjan Mamattursun

Abstract: Evapotranspiration (ET) is a key indicator of arid and semi-arid ecosystem processes and hydrological cycles. The study of basin-scale ET characteristics and drivers can provide a better understanding of regional water balance and energy cycles. This study used the Pixel Information Expert Engine platform based on MODIS (MOD16A2) data to extract the separate spatial and temporal characteristics of interannual and seasonal ET in the Urumqi River Basin in Xinjiang, China, over a 20-year period, from 2000 to 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(65 reference statements)
2
2
0
Order By: Relevance
“…The results showed that evapotranspiration varies proportionally with the impact of altitude on Kahramanmaras. The results support the findings of Lin et al [80] regarding ET correlation with topography in the Xiliao River Plain, while the outcomes are different from those reported by Ablikim et al [81], in which ET values rise with the increment in altitude in the Urumqi River Basin. For instance, the reason for the high ET values in S2, which has the lowest altitude of 525 m, is thought to be the adverse effect of altitude on ET.…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that evapotranspiration varies proportionally with the impact of altitude on Kahramanmaras. The results support the findings of Lin et al [80] regarding ET correlation with topography in the Xiliao River Plain, while the outcomes are different from those reported by Ablikim et al [81], in which ET values rise with the increment in altitude in the Urumqi River Basin. For instance, the reason for the high ET values in S2, which has the lowest altitude of 525 m, is thought to be the adverse effect of altitude on ET.…”
Section: Discussionsupporting
confidence: 83%
“…The obtained models show that in the functions where precipitation data is employed, the constants of the precipitation variable have a less effective coefficient than the other variables in the formulae. Ablikim et al [52] showed in their study the natural factors that had the greatest and least influences on forecasting evaporation belong to temperature and precipitation, respectively, which supports the aforementioned results. The climatic parameter-driven simulation is represented with the box and whisker plots.…”
Section: Discussionsupporting
confidence: 64%
“…Unfortunately, EP measurements are not available in half of the one-year period in Turkey and these values vary spatiotemporally. Alternative approaches have been investigated since EP measurements are expensive, complex, and time-consuming, [50][51][52]. Within the scope of this study, artificial intelligence techniques were used, which require less data and can be calculated relatively easily, and the use of which has increased with the convenience of developing technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation